Pengaruh Media Pop Up Book Terhadap Hasil Belajar Siswa pada Mata Pelajaran Matematika Kelas IV di SDN 3 Sumber - Regita Febryanti; Muhamad Khozinul Huda; Asih Wahyuningsih (CV. ULIL ALBAB CORP, 2024)
In learning activities, the role of a medium is very important. If in the learning process, the material taught is not understood by students, a teacher needs to use a medium. So that students can better understand the learning material well. The use of appropriate learning media in the learning process will achieve the success of learning objectives. One of the efforts made is the use of pop up book media in learning. The purpose of this study is to determine the use of pop up book media can work optimally in learning and determine the effect of pop up book media on students' math learning outcomes. This research method uses experimental quantitative methods. The population in this study were all students of SDN 3 Sumber, while the samples used were grade IV students. The research instruments used were observation sheets, pretest posttest question sheets, and documentation. The results of this study indicate that student learning outcomes are affected after the teacher uses pop up book media in the learning process. This can be seen from the average pretest result of 57.3. After being given treatment, the average student posttest result was 84.7. This shows that many students have exceeded the KKM score. So it can be concluded that by using pop up book media in learning, it has an effect on student learning outcomes in grade IV math subject.